2021
DOI: 10.3390/ijerph18168713
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution to Stress Recovery and Attention Restoration Potential of Exposure to Urban Green Spaces in Low-Density Residential Areas

Abstract: This study assessed the contributions of urban green spaces on mental health with joint consideration of people’s physiological and psychological responses. The psychological and physiological responses of participants aged between 22 and 28, who visited green spaces in a low-density area of Fuzhou, Fujian Province, China, were measured using Perceived Restorativeness Scale (PRS) methods and biometric wearable sensing devices, respectively. Results showed that exposure to green space led to significant changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 68 publications
2
27
1
1
Order By: Relevance
“…In rural areas, for example, the physiological reactions occur without extensive cognitive encoding, while participants in the urban areas expressed affective judgments, which were not related to the skin conductance level. Interestingly, the measured physiological responses are not correlated to the amount of green in the stimuli (Supplementary Table S4), and we even observed lower arousal values despite higher content of greenery, contrasting with results shown in other studies 24,38 . This might be due to a "misfit" between the amount of green and the meanings people ascribe to certain places.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In rural areas, for example, the physiological reactions occur without extensive cognitive encoding, while participants in the urban areas expressed affective judgments, which were not related to the skin conductance level. Interestingly, the measured physiological responses are not correlated to the amount of green in the stimuli (Supplementary Table S4), and we even observed lower arousal values despite higher content of greenery, contrasting with results shown in other studies 24,38 . This might be due to a "misfit" between the amount of green and the meanings people ascribe to certain places.…”
contrasting
confidence: 99%
“…Building on the seminal work of Ulrich 24 , studies have shown that stressful environments 25 or the type of neighborhoods influence physiological reactivity [26][27][28][29][30] . In particular, exposure to urban green 26,[31][32][33][34][35] and high biodiversity [36][37][38] have been shown to reduce stress, and natural sounds are more effective than traffic noise in fostering restorative experience 39 . The nature and role of bodily responses in the intentions to interact with places remains unclear.Measuring emotions in real-world contexts is highly challenging, as one cannot control exposures across individuals.…”
mentioning
confidence: 99%
“…While a sizeable body of neuroscience research exists highlighting the benefits of positive social interactions and environments that are more stimulating (albeit minimally) than a bare space, neuroscience has far less to say on the benefits of engagement with nature, and the impact of different colors, smells and textures on brain function and mental health. In contrast, architecture and design literature, as well as a wealth of multi-disciplinary research from geography and planning, sociology, public health, nursing, and psychology, has demonstrated the multiple health benefits of connection with nature, including reduced stress, psychological distress and depression, enhanced memory and cognitive development, and the promotion of general wellbeing [ 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ]. Conversely, a lack of green space, has been shown to negatively impact mental health and wellbeing [ 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, neuroscience tools have also been applied in research on indoor and outdoor plants. For example, scholars explored the effects of indoor plants on human comfort, mental stress, happiness as well as other physiological and psychological effects ( Hassan et al, 2020 ; Elsadek and Liu, 2021 ), and the effects of different plants and colors in outdoor green spaces and the layout of green landscape on mental health ( Huang et al, 2021 ).…”
Section: Knowledge Fusion Of Neuroscience Tools In Building Constructionmentioning
confidence: 99%